2 - Sous-développement de l'agriculture et pauvreté d'un pays pauvre (Cas du Zaïre) - M'BAYA, Kankuenda (Africa Development, 1980)
The author attempts to explain the paradoxical situation of the Zairian economy with its immense agricultural potential on the one hand and stagnation and underdevelopment of its agricultural production on the other hand. In the introductory part, the author shows the impor tance of agriculture to the Zairian economy in both the colonial and post independence period. In the colonial period, agricultural production experienced rapid growth and at the time of independence it accounted for 38 per cent of GNP which is high considering the importance of mineral production in Zaire. Colonial agriculture was based on a dualistic division of labour in which white settlers and foreign firms (backed by the colonial govern ments which provided them the necessary physical infrastructure) specia lized in export crops and the Africa small farmers specialized in staple food production usually under some form of coercion. Since independence agricultural production has declined dramati cally. Given the significant weight of agriculture in Zaire, this retrogres sion has had adverse effects on the overall performance of the economy. The author argues that the decline in agriculture was not only due to the inherent fragility of the policies pursued by the colonial governments and the weakness of the structures inherited by the new government but was also a consequence of policies pursued by the post-independence govern ment. After independence, the direct means of coercion available to the colonial government were no longer applicable nor did the political insta bility facilitate the maintenance of the infrastructure left behind by the colonial government. However, in addition to these constraints, there was a set of policy measures adopted by the government which was to ensure stagnation. In the first place, agricultural research continued to favour export crops although the level of allocation of funds to research insti tutes declined. Secondly, the prices paid to peasants were very low. Thirdly, adequate credit facilities were not extended to farmers. And, finally, there was no industrial policy clearly related to the policy of agri culture either by providing agriculture with essential inputs or by trans forming its output.